Morphology of oblique detonation waves in a stoichiometric hydrogen–air mixture. (19th February 2021) - Teng, Honghui; Tian, Cheng; Zhang, Yining; Zhou, Lin; Ng, Hoi Dick
Abstract: Abstract : Although the morphology of oblique detonation waves (ODWs) has been widely studied, it remains impossible to predict the wave systems in the initiation region, which is a critical component in promoting engine applications. Such wave systems are usually viewed as secondary ODWs or compression waves (CWs), introducing some structural ambiguities and contradictions with recent observations. In this study, ODWs are simulated numerically in a stoichiometric hydrogen–air mixture and their morphological features are analysed. To cover a wide range of flight conditions physically, the control parameters are the flight altitude H_0 and Mach number M_1 of an ODW-based engine. Numerical results reveal the morphological variations with respect to H_0 and M_1, within which two special wave systems arise. One wave system indicates that the CW might induce an abrupt transition, and the other indicates that the classical secondary ODW might evolve into a normal detonation wave, another illustration of the well-known 'detonation-behind-shock' wave configurations. To clarify the mechanism of wave system variation, a geometric analysis of two characteristic heights demonstrates that the wave system could be predicted from the viewpoint of CW convergence. Moreover, analysis of the induction zone Mach number, compared with the corresponding Chapman–Jouguet Mach number, provides a criterion for the normal detonation wave formation. These semi-theoretical approaches collectively enhance our understanding of the wave system physically.